Analisis Prioritas dan Strategi Perawatan Mesin Bubut Menggunakan Metode Failure Mode And Effect Analysis (FMEA) dan Diagram Pareto Di PT XYZ - Qanita Zahira Muhar Arifin; Akmal Suryadi (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
PT The lathe is one of the essential machines in production activities in this company. The amount of downtime caused by machine failure will reduce product quality and quantity. Therefore, this research aims to identify the factors that most influence the risk of lathe failure so that repair priorities and maintenance strategies can be determined. This can be achieved by using the Failure Mode and Effect Analysis (FMEA) method. FMEA is a method that can be used to identify the causes and impacts of each possible failure mode on machine components by systematically explaining the levels of failure so that appropriate prevention or repair can be carried out. The FMEA method shows the Risk Priority Number (RPN) value as a reference in determining the choice of maintenance strategy, namely, predictive maintenance, preventive maintenance or corrective maintenance. The research results show that the highest RPN value is found in the motor shaft pulley component at 320 and Nut Screw at 210. Maintenance priorities are determined based on the Pareto diagram principle. The appropriate maintenance strategy carried out by PT. Keywords: FMEA, Lathe, Maintenance, RPN